Comparing the efficiency of different kayaking paddle leaves - Esposito, G.; Schmid, M.; Guerra, B. M. V.; Bronzini, D.; Ramat, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Flatwater kayaking performance was revolutionized following the introduction of the "wing" paddle in 1986, which was significantly more efficient than the traditional "drag" one. Since then, many sports equipment manufacturers have proposed several new designs based on the "wing" paddle leaf concept, in an attempt to further improve performances. Yet, to our knowledge, no quantitative comparison of the efficiency of such new designs was carried out so far. Here we set out to experimentally compare two popular new paddle shapes and determine whether the different designs do have an effect on performance.